The E1B19K Oncoprotein Complexes with Beclin 1 to Regulate Autophagy in Adenovirus-Infected Cells - Piya, Sujan (Public Library of Science, 2011)
The mechanisms underlying adenovirus-mediated autophagy are currently unknown. Recently, members of the Bcl-2 protein family have been associated with autophagy. It was also reported that the Bcl-2 homology-3 (BH3) domain encompassed by both Beclin 1 and Bcl-2-like proteins is essential for their pro-autophagy or anti-autophagy functions. Here, we report for the first time that E1B19K, the adenovirus BH3 domain protein, interacts with Beclin 1 to initiate autophagy. Using immunoprecipitation assays we showed that expression of E1B19K in the host cell disrupted the physical interactions between Beclin 1 and Bcl-2 proteins. The displacement of Bcl-2 was coincident with the recruitment of PI3KC3 to the Beclin 1/E1B19K complexes. As a result of the changes in the components of the Beclin 1 interactome, there was activation of PI3KC3, as showed by the identification of PI3K-mediated lipid phosphorylation, and subsequent formation of autophagosomes. Importantly, the BH3 functional domain of E1B19K protein was required for the heterodimerization with Beclin 1. We also showed that transfer of E1B19K was sufficient to trigger autophagy in cancer cells. Consistent with these data, mutant adenoviruses encompassing a deletion of the E1B19K gene produced a marked deficiency in the capability of the virus to induce autophagy as showed by examining the lipidation and cleavage of LC3-I as well as the subcellular localization of LC3-II, the decrease in the levels of p62, and the formation of autophagosomes. Our work offers new information on the mechanisms of action of the adenoviral E1B19K protein as partner of Beclin 1 and positive regulator of autophagy.